High-temperature-resistant anti-corrosion concrete flue and preparation method thereof

By adopting a multi-layer structure in the flue, high-temperature corrosion-resistant concrete design, combined with aluminum sol, silicate cement and other materials, the corrosion problem of the flue in a high-temperature acid-base environment is solved, and efficient high-temperature resistance and penetration resistance is achieved. Performance, extends service life and improves structural stability.

CN119241161APending Publication Date: 2025-01-03HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324127.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing flue components are prone to corrosion under high temperature, acid, alkali, water, and oil and gas erosion, resulting in honeycombs, lint, shedding, and steel bars. In severe cases, it may lead to flue gas leakage and overall damage, affecting service life.

Method used

High-temperature corrosion-resistant concrete flue consisting of high-temperature corrosion-resistant layer, heat-resistant protective layer, heat-resistant anti-seepage layer and structural layer. The high-temperature corrosion-resistant anti-corrosion-resistant layer is composed of aluminum sol, silicate cement, potassium silicate, aluminum silicate , silicon carbide and nanotitanium dioxide, the thermal insulation protective layer consists of vitrified microbeads, fine ceramic particles, magnesium cement and casein, the heat-resistant and anti-seepage layer consists of chlorinated polypropylene resin and pervinyl chloride resin, and the structural layer is Using pretreated fine aggregates and steel fibers, the combination of these layers provides high temperature resistance, corrosion resistance and thermal insulation.

Benefits of technology

Effectively prevent the invasion of acid and alkali gases and water vapor, reduce heat transfer, improve the compressive strength and flexural strength of the structural layer, extend service life, enhance overall bonding and stability, avoid microcracks caused by high temperature differences, and ensure flue safety and long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005054910160000091
    Figure BDA0005054910160000091
  • Figure BDA0005054910160000101
    Figure BDA0005054910160000101
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and anti-corrosion concrete flue. The high-temperature-resistant anti-corrosion concrete flue sequentially comprises a high-temperature-resistant anti-corrosion layer, a heat insulation protection layer, a heat-resistant anti-seepage layer and a structural layer from inside to outside. Through the combined action of all the layers, acid-base gas and water vapor in smoke are effectively prevented from invading the structural layer, transfer of smoke heat is blocked, the surface temperature of the structural layer is made to be close to the environment temperature, and the problem that the structural durability is affected due to microcracks caused by thermal stress of the structural layer under the high-temperature-difference condition is effectively solved; therefore, the obtained concrete flue has the characteristics of high temperature resistance, corrosion resistance, strong bearing capacity and the like, is good in overall combinability, high in volume stability and long in service life, and is suitable for smoke discharge components of civil and industrial buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building engineering materials, and in particular to a high-temperature resistant and corrosion-resistant concrete flue and a preparation method thereof. Background Art

[0002] As the main pipeline component / member connecting the combustion equipment / facility to the chimney, the quality and performance of the flue are directly related to the safety of high-temperature equipment operation. Since the flue is subjected to the high-temperature and highly corrosive flue gas for a long time, the flue concrete components are in the corrosive environment of high temperature, acid, alkali, salt, water vapor, and oil vapor for a long time, which will cause honeycomb, rough surface, shedding, steel bar rust and other damages. In severe cases, it will cause flue gas leakage and even the entire flue to be destroyed, threatening the safety and service life of the flue. The existing flue component technology is mainly to increase the strength by sandwiching steel wire mesh and other reinforcing materials in the concrete or to use patterned plates to prefabricate metal flue components. There are also flue components that are treated by setting an inner lining layer in the concrete layer. However, after years of continuous use of flue components, the inner wall is still prone to corrosion, affecting its service life.

[0003] Therefore, it is very necessary to develop a high temperature resistant and corrosion resistant concrete flue to ensure the safety and long service life of flue components. Summary of the invention

[0004] In view of this, the present invention aims to provide a high temperature resistant and corrosion resistant concrete flue to solve the problems of poor high temperature resistance, corrosion resistance, durability and short service life of existing flues.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A high temperature resistant and anti-corrosion concrete flue, which comprises a high temperature resistant anti-corrosion layer, a heat insulation protective layer, a heat resistant anti-seepage layer and a structural layer from the inside to the outside of the flue;

[0007] The high temperature resistant anti-corrosion layer is a high temperature resistant anti-corrosion coating suitable for an acidic or alkaline environment of 500°C, and the thickness of the high temperature resistant anti-corrosion layer is 0.5-0.8mm;

[0008] The thermal insulation protective layer is an inorganic thermal insulation layer with a thermal conductivity of no more than 0.05 W / (m·K), and the thickness of the thermal insulation protective layer is 50-100 mm;

[0009] The heat-resistant and anti-seepage layer is an organic-inorganic composite heat-resistant and anti-seepage layer with an anti-seepage pressure greater than 2 MPa, and the thickness of the heat-resistant and anti-seepage layer is 0.05-0.08 mm;

[0010] The structural layer is a high-strength and high-toughness concrete structural layer with a compressive strength of not less than 100 MPa and a flexural strength of not less than 25 MPa.

[0011] Optionally, the heat-resistant anti-seepage layer is sprayed on the structural layer, and the heat-insulating protective layer is sprayed on the heat-resistant anti-seepage layer; and the high-temperature resistant anti-corrosion layer is sprayed on the heat-insulating protective layer.

[0012] Optionally, the high temperature resistant anticorrosion layer comprises the following components in parts by weight:

[0013] 100 parts of aluminum sol, 45-55 parts of ordinary Portland cement, 40-50 parts of potassium silicate, 25-35 parts of aluminum silicate, 15-20 parts of silicon carbide, 1-5 parts of nano titanium dioxide powder, and 5-25 parts of water. The solid content of the aluminum sol is 30%.

[0014] Optionally, the high temperature resistant anti-corrosion layer is a high temperature resistant anti-corrosion layer prepared by the following method:

[0015] The ordinary Portland cement, the potassium silicate, the aluminum silicate and the silicon carbide are mixed evenly, and then the aluminum sol is added and stirred evenly to obtain slurry A;

[0016] Ultrasonic dispersion of the nano titanium dioxide powder and the water to obtain a suspension B;

[0017] The suspension B is added to the slurry A and stirred evenly to obtain a high temperature resistant anticorrosion layer.

[0018] The present invention adopts aluminum sol with excellent high temperature resistance and corrosion resistance as the matrix material of the inorganic coating, and adopts ordinary silicate cement as the gelling material to provide sufficient mechanical properties. The aluminum sol is dispersed in the pores of the hardened cement slurry to form a high temperature protective film, which imparts good high temperature resistance. Potassium silicate and aluminum silicate high temperature resistant components are added to the coating to further improve the high temperature resistance. In addition, by introducing the nano-penetration filling effect of nano-titanium dioxide powder, it is filled in the micropores and microchannels in the coating, and then assisted by the effect of silicon carbide with high corrosion resistance, the obtained high temperature resistant anti-corrosion layer has excellent corrosion resistance and anti-penetration performance, and can continue to work in an acidic or alkaline environment of 500°C, breaking through the technical bottleneck that only high alumina cement can be used in traditional high temperature resistant environments.

[0019] Optionally, the thermal insulation protective layer comprises the following components in parts by weight:

[0020] 100 parts of ordinary Portland cement, 45-55 parts of magnesia cement, 20-30 parts of vitrified microspheres, 10-15 parts of fine ceramsite, 3-7 parts of tackifier, 1-5 parts of basalt fiber, 80-100 parts of water. The maximum particle size of the vitrified microspheres and fine ceramsite is not more than 1.18 mm, and the density is not more than 600 kg / m 3 ; The viscosity enhancer is industrial casein.

[0021] Optionally, the thermal insulation protective layer is a thermal insulation protective layer prepared by the following method:

[0022] The vitrified microspheres, the fine expanded clay, the ordinary Portland cement, the magnesia cement, the viscosity enhancer and the basalt fiber are put into a mixer, dry-mixed at a speed of 60 r / min for 30 seconds, and then the water is added while stirring. After all the water is added, stirring is continued for 60 seconds to obtain a heat insulating protective layer.

[0023] The present invention adopts two inorganic thermal insulation materials with low thermal conductivity, vitrified microspheres and fine ceramsite, as the main materials of the thermal insulation protective layer, which not only have good thermal insulation performance, but also have excellent temperature resistance and durability. Magnesium cement that prevents high-temperature cracking and ordinary silicate cement that provides strength are used as binders for the thermal insulation materials to make them have good mechanical properties. Casein with good anti-sagging performance is used as a viscosity enhancer to further improve the bonding performance and ensure the bonding force between the thermal insulation protective layer and other adjacent layers. The stress dispersion effect of basalt fiber ensures that the thermal insulation protective layer does not crack under a long-term large temperature gradient, thereby extending its thermal insulation life. Among them, its thermal conductivity is not higher than 0.05W / (m·K), which ensures that the high-temperature resistant and corrosion-resistant concrete flue of the present invention has good thermal insulation performance and avoids cracking of the structural layer caused by the large temperature difference between the inside and outside.

[0024] Optionally, the heat-resistant and anti-seepage layer comprises the following components in parts by weight:

[0025] 100 parts of chlorinated polypropylene resin, 40-60 parts of perchlorethylene resin, 10-20 parts of calcium stearate powder, 1-5 parts of silicon carbide fiber. The molecular weight of chlorinated polypropylene resin is 60000-80000; the chlorine content of perchlorethylene resin is 65%.

[0026] Optionally, the heat-resistant and anti-seepage layer is a heat-resistant and anti-seepage layer prepared by the following method:

[0027] The chlorinated polypropylene resin and the perchlorethylene resin are mixed and heated to 80-100° C. After they are completely melted, the calcium stearate powder and the silicon carbide fiber are added while stirring and stirred evenly to obtain a heat-resistant and impermeable layer.

[0028] The present invention adopts chlorinated polypropylene resin and perchlorethylene resin with good acid and alkali resistance to coat the inside of the structural layer to form an organic impermeable membrane, which further isolates the penetration of components in the smoke, and then by adding calcium stearate powder, it has both hydrophobic and oleophobic functions, blocking the invasion and penetration of water vapor and oil smoke, and then through the interweaving effect of silicon carbide fibers, the toughness and crack resistance of the heat-resistant impermeable layer are improved, and its service life is increased. The combined effect of the above makes its impermeability pressure greater than 2MPa, effectively protecting the structural layer from the corrosion of smoke.

[0029] Optionally, the structural layer comprises the following components by weight: 100 parts of 52.5 grade ordinary Portland cement, 15-20 parts of ultrafine powder, 80-120 parts of fine aggregate, 2-8 parts of high-performance water reducing agent, 0.1-0.5 parts of defoaming agent, 1-5 parts of steel fiber, and 20-30 parts of water. The ultrafine powder has a specific surface area of ​​not less than 800m 2 / kg of amorphous aluminum silicate powder; the fine aggregate is a continuously graded fine aggregate with a particle size between 4.75-0.045mm obtained by crushing, screening, washing and drying tailings, metallurgical slag or construction waste concrete; the high-performance water reducer is a polycarboxylic acid-based high-performance water reducer; the defoamer is a silicone defoamer; and the steel fiber is a galvanized steel fiber with an aspect ratio of 40-80.

[0030] Optionally, the structural layer is a structural layer prepared by the following method:

[0031] The fine aggregate, the 52.5 grade ordinary Portland cement, the ultrafine powder, the steel fiber, the high-performance water reducing agent, the defoaming agent and the water are put into a mixer, stirred at a low speed of 60 r / min for 60 seconds, then stirred at a high speed of 300 r / min for 30 seconds, and then stirred at a low speed of 60 r / min for 30 seconds, and cast into a hollow structure, demolded after curing for a period of time, and then standard cured to a specified age to obtain a structural layer.

[0032] The present invention adopts processed industrial solid waste and construction waste as aggregate of the high-strength concrete layer, effectively utilizes and disposes of the waste, while reducing the cost of the structural layer, and has good economy. In addition, through the interaction between the various raw material components, the present invention makes the obtained structural layer have a compressive strength of not less than 100 MPa and a flexural strength of not less than 25 MPa. The good mechanical properties and toughness it exhibits make it suitable for the preparation of load-bearing components of various building flues.

[0033] Compared with the prior art, the high temperature resistant and corrosion resistant concrete flue of the present invention has the following advantages:

[0034] 1. The high temperature resistant and corrosion resistant concrete flue of the present invention uses pretreated tailings, metallurgical slag or construction waste concrete as fine aggregate in its structural layer, which effectively absorbs industrial solid waste and construction waste, and has a 35d compressive strength of more than 100MPa and a flexural strength of more than 25MPa, and is suitable for load-bearing components of various building flues; the heat-resistant and anti-seepage layer adopts an organic-inorganic composite coating, which has both hydrophobic and oleophobic properties, prevents the leakage of various components in the flue gas, and completely blocks the flue gas in the inner layer of the flue; the heat-insulating protective layer adopts an inorganic thermal insulation mortar, the thermal conductivity of which is not higher than 0.05W / (m·K), and the high durability of the inorganic thermal insulation material is brought into play; the high temperature anti-corrosion layer adopts an inorganic coating, which has the characteristics of high temperature resistance, strong adhesion, oil resistance, and resistance to corrosion by strong oxidizing acids and alkalis. Through the joint action of various layers, the present invention effectively prevents acid-base gases and water vapor in the flue gas from invading the structural layer, and blocks the transfer of flue gas heat, so that the surface temperature of the structural layer is close to the ambient temperature, and effectively avoids the problem of microcracks in the structural layer caused by thermal stress under high temperature difference conditions, which in turn affects the durability of the structure. The resulting concrete flue has the advantages of strong bearing capacity, good overall bonding, high volume stability and long service life. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.

[0036] Example 1

[0037] A high temperature resistant and anti-corrosion concrete flue comprises a high temperature resistant anti-corrosion layer, a heat insulation protective layer, a heat resistant anti-seepage layer and a structural layer from the inside to the outside of the flue, and is specifically prepared by the following method:

[0038] 1) Preparation of structural layer: 80kg of fine aggregate, 100kg of 52.5 grade ordinary Portland cement, 15kg of ultrafine powder, 1kg of steel fiber, 2kg of high-performance water reducer, 0.1kg of defoamer and 30kg of water were put into a mixer in sequence, stirred at a low speed of 60r / min for 60s, then stirred at a high speed of 300r / min for 30s, and then stirred at a low speed of 60r / min for 30s, and poured into a mold to prepare a hollow structural layer. After demoulding for 24h, it was cured under standard conditions for 7d to obtain a high-strength and high-toughness concrete structural layer for bearing loads. The compressive strength and flexural strength were tested to be 106.6MPa and 25.9MPa respectively.

[0039] 2) Preparation of heat-resistant and impermeable layer: 100 kg of chlorinated polypropylene resin and 40 kg of perchlorethylene resin are added to a heating kettle, and the temperature is raised to 80-100° C. After all the resins are melted, 20 kg of calcium stearate powder and 5 kg of silicon carbide fiber are added while stirring, and after stirring evenly, they are sprayed inside the structural layer in step 1), and cooled to room temperature to obtain an organic-inorganic composite heat-resistant and impermeable layer with oleophobic and hydrophobic functions, which can be used to block the permeation channel of smoke and water vapor. The anti-permeability pressure is greater than 2.0 MPa after testing;

[0040] 3) Preparation of thermal insulation protective layer: 30 kg of vitrified microspheres, 10 kg of fine ceramsite, 100 kg of P·O52.5 grade ordinary Portland cement, 45 kg of magnesia cement, 3 kg of viscosity enhancer and 5 kg of basalt fiber were sequentially put into a mixer, dry-mixed at a speed of 60 r / min for 30 s, and then 80 kg of water was added while stirring. After all the water was added, stirring was continued for 60 s to obtain an inorganic thermal insulation layer slurry, which was sprayed inside the heat-resistant and anti-seepage layer in step 2) with a mortar sprayer, and cured at room temperature for 7 days to obtain an inorganic thermal insulation protective layer with a heat transfer reducing effect. The thermal conductivity of the inorganic thermal insulation protective layer obtained by testing was 0.045 W / (m·K);

[0041] 4) Preparation of high temperature resistant anticorrosion layer: 45kgP·O52.5 grade ordinary Portland cement, 40kg potassium silicate, 35kg aluminum silicate and 20kg silicon carbide are sequentially added into a mixer and mixed evenly, then 100kg aluminum sol is added and stirred evenly, and then a suspension consisting of 1kg nano titanium dioxide powder and 5kg water and dispersed by ultrasonic is added, and stirring is continued. After mixing evenly, the suspension is sprayed inside the heat insulation protective layer of step 3) to obtain a high temperature resistant anticorrosion layer with physical shielding and electrochemical protection effects, which can continuously work in an acidic or alkaline environment at 500°C.

[0042] In this embodiment, the thickness of the high temperature resistant anti-corrosion layer is 0.5 mm, the thickness of the heat insulation protection layer is 50 mm, and the thickness of the heat resistant anti-seepage layer is 0.05 mm.

[0043] In this embodiment, the fine aggregate is a continuously graded fine aggregate with a particle size between 4.75 mm and 0.045 mm obtained by crushing, screening, washing and drying the tailings; the high-performance water reducer is a polycarboxylic acid-based high-performance water reducer; the defoamer is a silicone defoamer; the steel fiber is a galvanized steel fiber with an aspect ratio of 60; the molecular weight of the chlorinated polypropylene resin is 65,000; the chlorine content of the perchlorethylene resin is 65%; the maximum particle size of the vitrified microspheres and fine ceramsite is not more than 1.18 mm, and the density is 586 kg / m 3 ; The thickener is industrial casein; the solid content of the aluminum sol is 30%.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that the raw materials of the high temperature resistant anticorrosion layer, the heat insulation protective layer, the heat resistant anti-seepage layer and the structural layer constituting the high temperature resistant anticorrosion concrete flue are different, specifically:

[0046] High temperature resistant anticorrosion layer: 100kg aluminum sol, 48kg P·O52.5 grade ordinary Portland cement, 43kg potassium silicate, 32kg aluminum silicate, 19kg silicon carbide, 2kg nano titanium dioxide powder, 10kg water;

[0047] Thermal insulation protective layer: 100kg of P·O52.5 grade ordinary Portland cement, 49kg of magnesia cement, 28kg of vitrified microspheres, 11kg of fine ceramsite, 4kg of tackifier, 4kg of basalt fiber, 85kg of water. The thermal conductivity of the thermal insulation protective layer of this embodiment is 0.043W / (m·K) after testing.

[0048] Heat-resistant and anti-seepage layer: 100kg of chlorinated polypropylene resin, 45kg of perchlorethylene resin, 18kg of calcium stearate powder, 4kg of silicon carbide fiber. The anti-seepage pressure is greater than 2MPa after testing.

[0049] Structural layer: 100kg of 52.5 grade ordinary Portland cement, 16kg of ultrafine powder, 90kg of fine aggregate, 4kg of high-performance water reducer, 0.2kg of defoaming agent, 2kg of steel fiber, and 28kg of water. The compressive strength was tested to be 112.8MPa and the flexural strength was 26.8MPa.

[0050] Moreover, in the present embodiment, the thickness of the high temperature resistant anti-corrosion layer is 0.6 mm, the thickness of the heat insulation protection layer is 60 mm, and the thickness of the heat resistant anti-seepage layer is 0.06 mm.

[0051] The other steps are the same as those in Example 1.

[0052] Example 3

[0053] The difference between this embodiment and embodiment 1 is that the raw materials of the high temperature resistant anticorrosion layer, the heat insulation protective layer, the heat resistant anti-seepage layer and the structural layer constituting the high temperature resistant anticorrosion concrete flue are different, specifically:

[0054] High temperature resistant anticorrosion layer: 100kg aluminum sol, 50kg P·O52.5 grade ordinary Portland cement, 45kg potassium silicate, 30kg aluminum silicate, 18kg silicon carbide, 3kg nano titanium dioxide powder, 15kg water;

[0055] Thermal insulation protective layer: 100kg of P·O52.5 grade ordinary Portland cement, 51kg of magnesia cement, 26kg of vitrified microspheres, 12kg of fine ceramsite, 5kg of tackifier, 3kg of basalt fiber, 90kg of water. The thermal conductivity of the thermal insulation protective layer of this embodiment is 0.042W / (m·K) after testing;

[0056] Heat-resistant and anti-seepage layer: 100kg of chlorinated polypropylene resin, 50kg of perchlorethylene resin, 15kg of calcium stearate powder, 3kg of silicon carbide fiber. The anti-seepage pressure is greater than 2MPa after testing;

[0057] Structural layer: 100kg of 52.5 grade ordinary Portland cement, 18kg of ultrafine powder, 100kg of fine aggregate (metallurgical slag), 5kg of high-performance water reducer, 0.3kg of defoaming agent, 3kg of steel fiber, and 26kg of water. The compressive strength was tested to be 122.3MPa and the flexural strength was 27.9MPa.

[0058] Moreover, in the present embodiment, the thickness of the high temperature resistant anti-corrosion layer is 0.65 mm, the thickness of the heat insulation protection layer is 70 mm, and the thickness of the heat resistant anti-seepage layer is 0.07 mm.

[0059] The other steps are the same as those in Example 1.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 1 is that the raw materials of the high temperature resistant anticorrosion layer, the heat insulation protective layer, the heat resistant anti-seepage layer and the structural layer constituting the high temperature resistant anticorrosion concrete flue are different, specifically:

[0062] High temperature resistant anticorrosion layer: 100kg aluminum sol, 53kg P·O52.5 grade ordinary Portland cement, 47kg potassium silicate, 27kg aluminum silicate, 16kg silicon carbide, 4kg nano titanium dioxide powder, 20kg water;

[0063] Thermal insulation protective layer: 100kg of P·O52.5 grade ordinary silicate cement, 53kg of magnesia cement, 22kg of vitrified microspheres, 14kg of fine ceramsite, 6kg of tackifier, 2kg of basalt fiber, 95kg of water. The thermal conductivity of the thermal insulation protective layer of this embodiment is 0.040W / (m·K) after testing;

[0064] Heat-resistant and anti-seepage layer: 100kg of chlorinated polypropylene resin, 55kg of perchlorethylene resin, 13kg of calcium stearate powder, 2kg of silicon carbide fiber. The anti-seepage pressure is greater than 2MPa after testing;

[0065] Structural layer: 100kg of 52.5 grade ordinary Portland cement, 19kg of ultrafine powder, 110kg of fine aggregate (construction waste), 7kg of high-performance water reducer, 0.4kg of defoaming agent, 4kg of steel fiber, and 23kg of water. After testing, its compressive strength is 129.3MPa and its flexural strength is 28.6MPa.

[0066] Moreover, in the present embodiment, the thickness of the high temperature resistant anti-corrosion layer is 0.7 mm, the thickness of the heat insulation protection layer is 85 mm, and the thickness of the heat resistant anti-seepage layer is 0.07 mm.

[0067] The other steps are the same as those in Example 1.

[0068] Example 5

[0069] The difference between this embodiment and embodiment 1 is that the raw materials of the high temperature resistant anticorrosion layer, the heat insulation protective layer, the heat resistant anti-seepage layer and the structural layer constituting the high temperature resistant anticorrosion concrete flue are different, specifically:

[0070] High temperature anti-corrosion layer: 100kg aluminum sol, 55kg P·O52.5 grade ordinary Portland cement, 50kg potassium silicate, 25kg aluminum silicate, 18kg silicon carbide, 5kg nano titanium dioxide powder, 25kg water;

[0071] Thermal insulation protective layer: 100kg of P·O52.5 grade ordinary Portland cement, 54kg of magnesia cement, 21kg of vitrified microspheres, 15kg of fine ceramsite, 7kg of tackifier, 1kg of basalt fiber, 99kg of water. The thermal conductivity of the thermal insulation protective layer of this embodiment is 0.037W / (m·K) after testing;

[0072] Heat-resistant and anti-seepage layer: 100kg of chlorinated polypropylene resin, 59kg of perchlorethylene resin, 11kg of calcium stearate powder, and 1kg of silicon carbide fiber. The anti-seepage pressure is greater than 2MPa after testing;

[0073] Structural layer: 100kg of 52.5 grade ordinary Portland cement, 20kg of ultrafine powder, 118kg of fine aggregate (construction waste), 8kg of high-performance water reducer, 0.5kg of defoaming agent, 5kg of steel fiber, and 20kg of water. After testing, its compressive strength is 132.5MPa and its flexural strength is 28.9MPa.

[0074] Moreover, in the present embodiment, the thickness of the high temperature resistant anti-corrosion layer is 0.8 mm, the thickness of the heat insulation protection layer is 100 mm, and the thickness of the heat resistant anti-seepage layer is 0.08 mm.

[0075] The other steps are the same as those in Example 1.

[0076] Comparative Example 1

[0077] The difference between this comparative example 1 and example 1 is that there is only the structural layer in example 1.

[0078] Comparative Example 2

[0079] The difference between this comparative example 1 and example 1 is that there are only the structural layer and the heat-resistant and impermeable layer in example 1.

[0080] Comparative Example 3

[0081] The difference between this comparative example 1 and example 1 is that there are only the structural layer, the heat-resistant anti-seepage layer and the heat-insulating protective layer in example 1.

[0082] The high temperature resistant and anti-corrosion concrete flues obtained in Examples 1-5 and Comparative Examples 1-3 were tested for thermal conductivity, water seepage pressure, mechanical properties, mechanical properties after acid and alkali immersion, and mechanical properties under high temperature conditions, and the results are shown in Table 1.

[0083] Among them: the mechanical properties are the compressive strength and flexural strength of the structural layer under standard curing conditions for 35 days; the acid and alkali soaking is soaked in 1 mol / L sulfuric acid and sodium hydroxide solution respectively. After curing for 28 days under standard conditions for Examples 1-5 and Comparative Examples 1-3, the exterior and sides of the structural layer are coated with paraffin for protection, and then soaked in acid and alkali solutions for 7 days, and then the high-temperature anti-corrosion layer, heat-insulating protective layer, and heat-resistant anti-seepage layer are removed to test the mechanical properties. Before testing the mechanical properties under high temperature conditions, the exterior and sides of the structural layer of the concrete flue cured under standard conditions for 35 days are sealed with high-temperature resistant asbestos for protection, and then placed in an electric furnace at 500°C for 60 minutes, the electric furnace is turned off, and after cooling to room temperature, the high-temperature anti-corrosion layer, heat-insulating protective layer, and heat-resistant anti-seepage layer are removed to test the mechanical properties.

[0084] It can be seen from Table 1 that the structural layer of Examples 1-5 of the present invention has excellent performance under the overall effect of the heat-resistant anti-seepage layer, the heat-insulating protective layer, and the high-temperature resistant anti-corrosion layer. Comparative Example 1 is only a structural layer, and its mechanical properties are significantly reduced under acid, alkali and high-temperature environments, and its heat insulation and anti-seepage capabilities are also poor. Comparative Example 2 adds a heat-resistant anti-seepage layer on the basis of Comparative Example 1, which significantly improves the anti-seepage performance, and improves the acid and alkali erosion resistance to a certain extent; Comparative Example 3 adds a heat-insulating protective layer on the basis of Comparative Example 2, which significantly improves the heat insulation performance, and improves the mechanical properties under high temperature conditions to a certain extent. In summary, the heat insulation performance, acid and alkali erosion resistance, mechanical properties, high temperature resistance, etc. of the high-temperature resistant and anti-corrosion concrete flue obtained in the embodiments of the present invention are better than those of ordinary concrete flues.

[0085] Table 1 Performance test results of the anticorrosive concrete flues obtained in Examples 1-5 and Comparative Examples 1-3

[0086]

[0087]

[0088] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature resistant and anti-corrosion concrete flue, characterized in that: From the inside to the outside of the flue, there are high temperature resistant anti-corrosion layer, heat insulation protection layer, heat resistant anti-seepage layer and structural layer; The high temperature resistant anti-corrosion layer is a high temperature resistant anti-corrosion coating suitable for an acidic or alkaline environment of 500°C, and the thickness of the high temperature resistant anti-corrosion layer is 0.5-0.8mm; The thermal insulation protective layer is an inorganic thermal insulation layer with a thermal conductivity of no more than 0.05 W / (m·K), and the thickness of the thermal insulation protective layer is 50-100 mm; The heat-resistant and anti-seepage layer is an organic-inorganic composite heat-resistant and anti-seepage layer with an anti-seepage pressure greater than 2 MPa, and the thickness of the heat-resistant and anti-seepage layer is 0.05-0.08 mm; The structural layer is a high-strength and high-toughness concrete structural layer with a compressive strength of not less than 100 MPa and a flexural strength of not less than 25 MPa.

2. The high temperature resistant and anti-corrosion concrete flue according to claim 1, characterized in that: The heat-resistant anti-seepage layer is sprayed on the structural layer, and the heat-insulating protective layer is sprayed on the heat-resistant anti-seepage layer; the high-temperature resistant anti-corrosion layer is sprayed on the heat-insulating protective layer.

3. The high temperature resistant and anti-corrosion concrete flue according to claim 1, characterized in that: The high temperature resistant anticorrosion layer comprises the following components by weight: 100 parts of alumina sol, 45-55 parts of ordinary Portland cement, 40-50 parts of potassium silicate, 25-35 parts of aluminum silicate, 15-20 parts of silicon carbide, 1-5 parts of nano titanium dioxide powder, and 5-25 parts of water.

4. The high temperature resistant and anti-corrosion concrete flue according to claim 3 is characterized in that: The high temperature resistant anti-corrosion layer is a high temperature resistant anti-corrosion layer prepared by the following method: The ordinary Portland cement, the potassium silicate, the aluminum silicate and the silicon carbide are mixed evenly, and then the aluminum sol is added and stirred evenly to obtain slurry A; Ultrasonic dispersion of the nano titanium dioxide powder and the water to obtain a suspension B; The suspension B is added to the slurry A and stirred evenly to obtain a high temperature resistant anticorrosion layer.

5. The high temperature resistant and anti-corrosion concrete flue according to claim 1, characterized in that: The thermal insulation protective layer comprises the following components in parts by weight: 100 parts of ordinary Portland cement, 45-55 parts of magnesia cement, 20-30 parts of vitrified microspheres, 10-15 parts of fine ceramsite, 3-7 parts of viscosity enhancer, 1-5 parts of basalt fiber, and 80-100 parts of water.

6. The high temperature resistant and anti-corrosion concrete flue according to claim 5, characterized in that: The thermal insulation protective layer is a thermal insulation protective layer prepared by the following method: The vitrified microspheres, the fine expanded clay, the ordinary Portland cement, the magnesia cement, the viscosity enhancer and the basalt fiber are put into a mixer, dry-mixed at a speed of 60 r / min for 30 seconds, and then the water is added while stirring. After all the water is added, stirring is continued for 60 seconds to obtain a heat insulating protective layer.

7. The high temperature resistant and anti-corrosion concrete flue according to claim 1, characterized in that: The heat-resistant and anti-seepage layer comprises the following components in parts by weight: 100 parts of chlorinated polypropylene resin, 40-60 parts of perchlorethylene resin, 10-20 parts of calcium stearate powder, and 1-5 parts of silicon carbide fiber.

8. The high temperature resistant and anti-corrosion concrete flue according to claim 7, characterized in that: The heat-resistant and anti-seepage layer is a heat-resistant and anti-seepage layer prepared by the following method: The chlorinated polypropylene resin and the perchlorethylene resin are mixed and heated to 80-100° C. After they are completely melted, the calcium stearate powder and the silicon carbide fiber are added while stirring and stirred evenly to obtain a heat-resistant and impermeable layer.

9. The high temperature resistant and anti-corrosion concrete flue according to claim 1, characterized in that: The structural layer comprises the following components by weight: 100 parts of 52.5 grade ordinary Portland cement, 15-20 parts of ultrafine powder, 80-120 parts of fine aggregate, 2-8 parts of high-performance water reducing agent, 0.1-0.5 parts of defoaming agent, 1-5 parts of steel fiber, and 20-30 parts of water.

10. The high temperature resistant and anti-corrosion concrete flue according to claim 9, characterized in that: The structural layer is a structural layer prepared by the following method: The fine aggregate, the 52.5 grade ordinary Portland cement, the ultrafine powder, the steel fiber, the high-performance water reducing agent, the defoaming agent and the water are put into a mixer, stirred at a low speed of 60 r / min for 60 seconds, then stirred at a high speed of 300 r / min for 30 seconds, and then stirred at a low speed of 60 r / min for 30 seconds, and cast into a hollow structure, demolded after curing for a period of time, and then standard cured to a specified age to obtain a structural layer.